Vom Monitoring zum Controlling: Weiterentwicklung von Nachhaltigkeitsindikatoren für die Regionalplanung am Beispiel eines Monitoring- und Controllingsystems „Gewerbeflächen” — Fallbeispiel Ostthüringen - Birkmann, Jörn (Raumforschung und Raumordnung | Spatial Research and Planning, 2003)
Sustainability indicators are regarded as vital instruments for the successful implementation of sustainable spatial development. However, many previous approaches have limited themselves to an essentially descriptive or reporting function. The fact that many concepts fail to go beyond enumerating desirable indicators has meant that in most cases these indicators do not end up being properly integrated within the planning and decision-making processes of regional and state-level spatial planning. This article discusses a number of possible ways of refining sustainability indicators as demonstrated by a monitoring and controlling system for the land-use type “commercial space”. Whereas other studies on the topic of regional sustainability indicators have tended to concentrate primarily on the goal of regional comparisons and rankings, the approach discussed here aims to show how indicators may be put to use as tools within the planning process. Consequently, the monitoring- and controlling-based approach is not presented simply in abstract or theoretical terms, but is rather underpinned by a review of the results of its application in the Eastern Thuringia region as an illustration of the benefits it promises for planning practice.